Electoral rules, political competition and fiscal spending: regression discontinuity evidence from Brazilian municipalities - Marcos Chamon; Jo\~ao M. P. de Mello; Sergio Firpo (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2008)
We exploit a discontinuity in Brazilian municipal election rules to investigate whether political competition has a causal impact on policy choices. In municipalities with less than 200,000 voters mayors are elected with a plurality of the vote. In municipalities with more than 200,000 voters a run-off election takes place among the top two candidates if neither achieves a majority of the votes. At a first stage, we show that the possibility of runoff increases political competition. At a second stage, we use the discontinuity as a source of exogenous variation to infer causality from political competition to fiscal policy. Our second stage results suggest that political competition induces more investment and less current spending, particularly personnel expenses. Furthermore, the impact of political competition is larger when incumbents can run for reelection, suggesting incentives matter insofar as incumbents can themselves remain in office.
Keywords: 330; Electoral Systems; Strategic Voting; Political Competition; Regression Discontinuity; Fiscal Spending. JEL Codes: H72; D72; C14; P1; Kommunale Finanzpolitik; Neue politische Ökonomie; Kommunalwahl; Wahlsystem; Schätzung; Brasilien